Efisiensi Teknis Padi Lahan Kering Hibrida dan Inbrida di Kabupaten Lampung Tengah - Nurhasan, Nurhasan; Prasmatiwi, Fembriarti Erry; Murniati, Ktut (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Based on observations in the field, many farmers have not achieved efficiency in the farming businesses they run, both technically and economically, which has an impact on low productivity. The purpose of this research is to examine income levels and factors that influence production in rice farming businesses, as well as analyzing technical efficiency in hybrid and inbred rice farming businesses on dry land.  The location was carried out purposively in Central Lampung Regency, this research used survey methodology. The sample for this research was 70 hybrid rice farmers and 70 inbred rice farmers who were selected using probability sampling.  Quantitative analysis is used to determine the amount of income to achieve research objectives. Stochastic frontier production function analysis techniques are used to measure technological efficiency and determine the variables that influence it. Based on research findings, rice cultivation on dry land is beneficial if the R/C value is higher than one.  The production of dryland hybrid rice varieties was strongly influenced by land area, seeds, urea fertilizer and manure, meanwhile, the production of inbred dryland rice varieties was strongly influenced by land area, labor and urea fertilizer. Technically, dry land rice farming is quite efficient.  In Central Lampung Regency, dry land rice cultivation is considered very productive for hybrid rice and quite productive for inbred rice. Meanwhile, production variables, land rental prices, and labor wages influence the costs of inbred rice farming, production variables, land rental prices, and NPK fertilizer prices influence the total costs of hybrid rice farming.